Character Formation of Muslim Children Through Indigenous Education in Stone Floor Elementary Schools - pahar kurniadi; Musyarrafah Sulaiman Kurdi; Nofri Yudi Arifin; Wily Mohammad (Journal Emerging Technologies in Education, 2023)
Background. This study examines the character formation of Muslim children through indigenous education at Floor IT Elementary School, Batusangkar, Tanah Datar Regency. The problem lies in the character formation of Muslim children. Purpose. From this problem, the question arises about the condition of the students' character and what efforts the teacher has made to shape the students' character at the Sekolah IT Floor Batu. This research is field research because the researcher directly visited the research subjects. Method. Data was obtained through direct observation and interviews with teachers at the school. After the data is collected, it is then processed by classifying the data and making notes about the results of observations and interviews. Results Next, the data is narrated descriptively. The research results are discussed using theories which are also supported by the arguments of the Koran and Hadith as well as several applicable government regulations. This research found an important understanding that Indigenous education is an educational method that is based on customs or customs that develop in society. Children's characters emerge due to the influence of the customs of the place where they live. Conclusion. To prevent the emergence of bad characters, teachers gather their students in one environment, so that teachers can accustom children to behave well. In this way, teachers can shape the character of Muslim children and familiarize children with behaving according to the character of Muslim children